PENGARUH LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS PADA PT BANK SULSELBAR MAKASSAR - Indrawan Azis (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
This research aims to analyze the influence of the loan to deposit ratio (LDR) to wards banking profitability as measured by return on assets (ROA) at PT Bank SulSelBar Makassar. The Bank is a financial institution whose primary activity is to raise funds from the public and then channel it with the intention to earn income. The purpose of this research was to prove the influence of loan to deposit ratio (LDR) towards return on Asset (ROA). Data obtained from the financial reports quarterly publication published by PT Bank SulSelBar Makassar with a period of time in 2011 to 2013. Analytical techniques used in this research is a simple linear regression to obtain an idea of the relationship of one variable with another variable. From the results of the research indicate that the Loan To Deposit Ratio (LDR) has no effect on the Return On Assets (ROA).